2020
DOI: 10.18632/aging.103595
|View full text |Cite
|
Sign up to set email alerts
|

Megakaryocytes promote osteoclastogenesis in aging

Abstract: Megakaryocytes (MKs) support bone formation by stimulating osteoblasts (OBs) and inhibiting osteoclasts (OCs). Aging results in higher bone resorption, leading to bone loss. Whereas previous studies showed the effects of aging on MK-mediated bone formation, the effects of aging on MK-mediated OC formation is poorly understood. Here we examined the effect of thrombopoietin (TPO) and MK-derived conditioned media (CM) from young (3-4 months) and aged (22-25 months) mice on OC precursors. Our findings showed that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 49 publications
(61 reference statements)
3
5
0
Order By: Relevance
“…The TPO concentration was based on our previous studies demonstrating increased osteoclast formation in BM Mφ. ( 34,35 ) In agreement with our published report, ( 34 ) TPO led to an increase in osteoclast formation by neonatal BM Mφ at two different plating densities (Fig. 5 B , C ).…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…The TPO concentration was based on our previous studies demonstrating increased osteoclast formation in BM Mφ. ( 34,35 ) In agreement with our published report, ( 34 ) TPO led to an increase in osteoclast formation by neonatal BM Mφ at two different plating densities (Fig. 5 B , C ).…”
Section: Resultssupporting
confidence: 92%
“…( 31,35 ) We also reported that unsorted macrophages from bone marrow stimulated with TPO form more osteoclasts than controls. ( 34,35 ) In the current study, we demonstrated that although neonatal OM express higher levels of CD110 than neonatal BM Mφ (Figs. 1 and 2D and Supplemental Table S3), OM did not undergo TPO‐stimulated increase in osteoclast formation, which was observed in the BM Mφ cultures (Fig.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…K562 cells were differentiated into mature MKs in phorbol 12-myristate 13-acetate (PMA)-supplemented medium for 7 days [ 26 ]; differentiation was determined by morphological changes, such as an increased nuclear/cytoplasmic ratio, large and multilobulated nuclei, and strong adhesion. Based on several reports that MKs may indirectly contribute to skeletal homeostasis [ 12 , 27 ], we investigated the effects of MK CM on osteoclast differentiation. Using tartrate-resistant acid phosphatase (TRAP) staining, TRAP-positive osteoclasts can be distinguished from TRAP-negative MKs [ 28 ].…”
Section: Resultsmentioning
confidence: 99%
“…With aging, the number of MKs increases, and the direct effect of MKs on promoting bone formation in osteoblasts is suppressed [ 34 ]. Increased MKs in aged mice activate RANKL expression and signaling, thereby promoting osteoclastogenesis and bone resorption activity [ 27 ]. Another study showed that MK CM regulates osteoblast and osteoclast differentiation and increases bone mass in ovariectomized mouse models, although the MK-secreted factors in MK CM have not been identified [ 12 ].…”
Section: Discussionmentioning
confidence: 99%